PENGARUH DUKUNGAN TOP MANAGEMENT, PELATIHAN PENGGUNA SIA, KEMAMPUAN TEHNIK PERSONAL SIA TERHADAP KEPUASAN PENGGUNA SIA (Studi Empiris pada PT. Bank Sulteng) - Amalia, Rizki (Katalogis, 2016)
This study aims to determine the effect of top management support, AIS user training, and AIS personal technical capabilities to the AIS user satisfaction on PT. Bank Sultenng, Palu Central Sulawesi. This research subject is the headquarters of PT Bank Central Sulawesi and one of the branches of service PT. Bank Sulteng branch Donggala, Central Sulawesi. The populations in this study were all employees whose job is directly related to the use of AIS on the headquarters and branch offices that is the subject of this study. The sampling technique in this research is census, because the total population of 47 people who are still allowed to do the census. This study used a questionnaire as a research instrument and multiple linear regression analysis as the statistical test data processing. The result showed that the support of top management, AIS user training, AIS personal technical capability, have a significant effect on the AIS satisfaction users simultaneously. Top management support and AIS user training are effect on AIS user satisfaction partially. AIS personal technical ability variable does not affect the AIS user satisfaction. Based on the value of Adjusted R Square AIS user satisfaction not only influenced by the variable support of top management, AIS user training, AIS personal technical capability, but is also influenced by other variables that not examined in this study, so expected for further research can add other variables that affect user satisfaction SIA other than those examined in this study.